A method for solving rectangular beams and discs = Metoda rozwiązywania prostokątnych ortotropowych belek i tarcz - Olejniczak, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An analytic method for solving two-dimensional elasticity problems of orthotropic body has been worked out. A solution for rectangular elements of the beam or disc type has been developed. This solution satisfies the fundamental equations of the elasticity theory of two-dimensional body exactly and the boundary conditions with large accuracy.
Keywords: teoria sprężystości; belka; tarcza ortotropowa; ortotropia; tick plate; beam; disc; orthotropy; analytic method